Quality of life and subjective well-being comparison between traumatic, nontraumatic chronic spinal cord injury, and healthy individuals in China - Ruba Altahla; Jamal Alshorman; Sayed Zulfiqar Ali-Shah; Mohammad Nasb; Xu Tao (PeerJ)
Background Differentiating between traumatic and non-traumatic spinal cord injuries (NT-SCI) is critical, as these classifications may significantly impact patients’ health outcomes and overall well-being, potentially resulting in differences in treatment protocols and therapeutic efficacy. Objective This study aims to compare the quality of life (QoL) and satisfaction with life (SWL) among individuals with traumatic spinal cord injuries (T-SCI), NT-SCI, and the healthy population in China. Method A quantitative, cross-sectional survey was conducted between July and December 2020 in the Rehabilitation and Physiotherapy Department of Tongji Hospital, Hubei University of Science and Technology. The World Health Organization Quality of Life Brief Version (WHOQOL-BREF) and the Satisfaction with Life Scale (SWLS) were administered to evaluate QoL and subjective well-being (SWB). An independent t-test was performed to assess differences within the SCI population, while Pearson’s correlation coefficient was utilized to explore relationships between the WHOQOL-BREF domains and the SWLS. Multiple linear regression analysis was applied to identify key determinants influencing World Health Organization Quality of Life (WHOQOL) domain scores and overall SWLS score. Result Participants with NT-SCI exhibited significant differences in overall health as measured by the WHOQOL-BREF domains compared to those with T-SCI (p < 0.05). Both the NT-SCI and T-SCI groups demonstrated lower mean scores across all four WHOQOL-BREF domains compared to healthy individuals. No significant differences were observed between the NT-SCI and T-SCI groups in the SWLS, although both groups scored lower than the healthy population. Additionally, SWB was moderately positively correlated with QoL (p < 0.01). Collectively, the predictor variables explained 22.28% of the variance in physical health, 6.43% in psychological health, 28.67% in social health, and 25.68% in environmental health. Furthermore, the independent variables accounted for approximately 22.67% of the variance in the SWLS. Conclusions Individuals with NT-SCI experience significantly worse overall health outcomes compared to those with T-SCI, although both groups report QoL and life satisfaction than healthy individuals. No significant differences in life satisfaction were found between two groups. Additionally, SWB shows a moderate positive correlation with QoL, highlighting the close relationship between mental and physical health in SCI populations.